Complex data warehousing and knowledge discovery for advanced retrieval development innovative methods and applications - Nguyen, Tho Manh.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
This book provides a comprehensive analysis on current issues and trends in retrieval expansion. Containing research from leading international experts, this book presents future challenges and opportunities in the field valuable to academicians, researchers, and practitioners.
DWH architectures and fundamentals -- Multidimensional data and OLAP -- DWH and OLAP applications -- Data mining techniques -- Advanced mining applications -- Compilation of references -- About the contributors -- Index.
Includes bibliographical references (p. 361-388) and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 19, 2010).
Keywords: Data warehousing; Database searching; Calendar-based pattern mining; Cost-sensitive decision trees; Data mining techniques; Data warehousing systems; Decisional annotations; Deploying data warehouses in grids; Encrypted network streams; Federated data warehouses; Multidimensional systems; OLAP databases; Ranking gradients in multi-dimensional spaces; Scalable indexing and storage; Spatial data warehouses; Electronic books